2005
DOI: 10.1002/mrd.20266
|View full text |Cite
|
Sign up to set email alerts
|

Unequal segregation of parental chromosomes in embryonic stem cell hybrids

Abstract: Chromosome segregation was studied in 14 intra- and 20 inter-specific hybrid clones generated by fusion of Mus musculus embryonic stem (ES) cells with fibroblasts or splenocytes of DD/c mice or Mus caroli. As a control for in vitro evolution of tetraploid karyotype we used a set of hybrid clones obtained by fusion of ES cells (D3) with ES cells (TgTP6.3). Identification of the parental chromosomes in the clones was performed by microsatellite analysis and in situ hybridization with labeled species-specific pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
1
23
1
Order By: Relevance
“…Unequal segregation of chromosomes and even a degree of chromosome selectivity in this process favoring the embryonic chromosomes (ie, loss of somatic chromosomes) has been reported. 51 It is therefore possible that the complete somatic genome contingent of somatic/ESC hybrid cells may not be represented in the teratoma cells, and this might lead to false impressions of genome reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Unequal segregation of chromosomes and even a degree of chromosome selectivity in this process favoring the embryonic chromosomes (ie, loss of somatic chromosomes) has been reported. 51 It is therefore possible that the complete somatic genome contingent of somatic/ESC hybrid cells may not be represented in the teratoma cells, and this might lead to false impressions of genome reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the chromosomal makeup of both interspecies (Matveeva et al 1998(Matveeva et al , 2005Vasilkova et al 2007) and intraspecies (Matveeva et al 2005;Vasilkova et al 2007) of ES-somatic hybrids demonstrated that most ES cell markers were present for most chromosomes, while somatic markers were present only for a few chromosome pairs suggesting that the somatic chromosomes were preferentially lost. This unequal segregation of parental chromosomes and preferential loss of somatic chromosomes observed in some interand intraspecies mouse ES-somatic cell hybrids suggest that pluripotential is maintained by the ES chromosomes in a cisacting and not in a trans-acting manner (Vasilkova et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, the DNA content of triploid V79 Chinese hamster lung cells that were established from diploid cells was stable during long-term culturing (FujikawaYamamoto et al 2002). Matveeva et al (2005) reported that the chromosome number was stable in (ES cell)-(ES cell) hybrids, but not in (ES cell)-(somatic cell) hybrids. We were interested in whether or not the DNA content decays in tetraploid ES cells in differentiate circumstances.…”
mentioning
confidence: 99%